Morphological Characterization of Five Newly Developed Lines of Arabica Coffee as Compared to Commercial Cultivars in Kenya - Gichimu, Bernard M.; Omondi, C. O. (ACADEMIC JOURNALS, 2010)
Five new lines of Arabica coffee and two existing commercial cultivars planted in the field were characterized morphologically. The objective of this study was to determine the level of morphological variation within and between new and existing coffee varieties in Kenya. Morphological characterization was done using a 25 character coffee descriptors. Both quantitative and qualitative morphological traits were recorded and the binary data were subjected to cluster and principal component analysis. Morphological variation among the genotypes was less than 25%. Four main groups were formed when the similarity index was considered for clustering. The improved cultivar, Ruiru 11 and the traditional cultivar SL28 were clustered alone in separate clusters, while two new lines CR8 and CR30 clustered together. The other three new lines CR22, CR23 and CR27 also clustered together in shared sub-clusters. As expected there was very little morphological variation within the varieties. In the principal component analysis, Ruiru 11 separated clearly from the rest and was located on the lower side of the PCA graph. SL28 was grouped with the new lines on the upper part of the PCA graph. The first two principal components accounted for a cumulative variance of 60%. The study demonstrated low morphological variation and hence low genetic variation among the varieties and emphasized the need to broaden the genetic base of Arabica coffee in Kenya. In addition, the study demonstrated minimal morphological variation within the varieties indicative of high genetic consistency.
Keywords: Genetic variability, varieties, Ruiru 11, SL28